Ferroptosis: A new therapeutic target for bladder cancer - Zeng, Fan; Lan, Yunping; Wang, Ning; Huang, Xiaobo; Zhou, Qiao; Wang, Yi (Frontiers in Pharmacology, 2022)
Bladder cancer (BC) is the most frequent type of urinary system cancer. The prognosis of bladder cancer is poor due to the high metastasis rates and multidrug resistance. Hence, the development of novel therapy targeting the cell death of BC is in urgent need. As a novel kind of cell death with strong antitumor potentials, ferroptosis has been the investigated in many groups for its potential for BC treatment. Characterized with iron-dependent cell death, ferroptosis is marked by excessive oxidative phospholipids. The molecular mechanisms of ferroptosis includes iron overload, System Xc-GSH-GPX4 signaling pathway and etc. Recent researcher revealed that ferroptosis is involved in the metastasis, treatment and prognosis of bladder cancer. Herein, in this review, we comprehensively summarized the mechanism of ferroptosis, addressed the newly identified targets of ferroptosis, and provided the potential of new clinical therapies in BC.